2019
DOI: 10.1111/nep.13642
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical value of gastrin‐releasing peptide precursor in nephropathy and chronic kidney disease

Abstract: Aim To explore whether serum pro‐gastric releasing peptide (proGRP) is elevated in nephropathy patients and evaluate the diagnostic value of proGRP in chronic kidney disease (CKD) patients. Methods A total of 498 nephropathy patients and 170 healthy were selected in Zhongshan Hospital, Medical College of Xiamen University, from February 2016 to September 2017. The clinical data of the different groups including serum proGRP, CKD grading, and other serum and urine renal function biomarkers were analyzed by grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The tumor markers showed limited diagnostic value with the AUC of CYFRA21‐1, ProGRP, CEA, NSE, and SCCA was 0.506, 0.503 0.532, 0.548, and 0.562, respectively. A previous study has reported that chronic kidney disease may cause an increase in ProGRP 21 . In addition, CYFRA 21‐1, CEA, and NSE also were reported to be possibly increased in non‐neoplastic conditions 10 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The tumor markers showed limited diagnostic value with the AUC of CYFRA21‐1, ProGRP, CEA, NSE, and SCCA was 0.506, 0.503 0.532, 0.548, and 0.562, respectively. A previous study has reported that chronic kidney disease may cause an increase in ProGRP 21 . In addition, CYFRA 21‐1, CEA, and NSE also were reported to be possibly increased in non‐neoplastic conditions 10 .…”
Section: Discussionmentioning
confidence: 93%
“…There was a trend of increasing incidence in young patients, and it was necessary to identify the di- previous study has reported that chronic kidney disease may cause an increase in ProGRP. 21 In addition, CYFRA 21-1, CEA, and NSE also were reported to be possibly increased in non-neoplastic conditions. 10 In summary, for young patients with pulmonary nodules, negative tumor markers should not be relaxed, while with elevated tumor markers, a comprehensive judgment should be made based on clinical, imaging, and other indicators to exclude benign lesions and avoid unnecessary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma GRP levels increase significantly in the rat model of nephrectomy-induced uremia or adenine‐induced CKD ( 12 ). Recently, serum proGRP levels have been reported to be considerably elevated in acute renal injury and in patients with CKD, and they increase with the severity of CKD ( 30 ). We demonstrated the elevated level of NMB in the serum of the CKD rat model.…”
Section: Discussionmentioning
confidence: 99%